When texts are canonized - Lim, Timothy H. (Providence, RI : Brown Judaic Studies, 2017)
"This volume examines two interconnected topics related to the canonization of authoritative scriptures. How did canonization take place, and what difference does it make to a text once it is canonized? Some of the papers probe the canonical process: Why were certain books, but not others, included in the canon? What criteria were used to select the books of the canon? Was canonization a divine fiat or human act? What was the nature of the authority of the laws and narratives of the Torah? How did prophecy come to be included in the canon? Others reflect on the consequences of canonization: What are the effects in elevating certain writings to the status of "Holy Scriptures"? What happens when a text is included in an official list? What theological and hermeneutical questions are at stake in the fact of the canon? Should the canon be unsealed or reopened to include other writings?"--
An indicative definition of the Canon / Timothy H. Lim -- The way of God: early Canonicity and the "Non-deviation formula" / Manfred Oeming -- Uses of Torah in the Second Temple period / John J. Collins -- Bad prophecies: Canon and the case of the Book of Daniel / Michael L. Satlow -- Canon and content / John Barton -- Jesus and the beginnings of the Christian Canon / Craig A. Evans -- Canon and religious truth: an appraisal of a new New Testament / R.W.L. Moberly.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Bible -- Canon; Canonization; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Electronic books